A class of one: Students' satisfaction with online learning. Issue 2 (17th February 2021) - Landrum, Brittany; Bannister, Jennifer; Garza, Gilbert; Rhame, Susan
Abstract: This study explores how students evaluate their satisfaction with online classes. Data from three focus groups of undergraduate and graduate students was analyzed using Thematic Collation and Thematic Analysis to illuminate how students evaluate their satisfaction with online classes. Student satisfaction with online learning emerged as a lived consonance, that is a "gearing together" of student concerns. The main dimensions of these concerns are student expectations regarding the time and space of online learning, self-motivation, and the role of others, including fellow students and the teacher. Ultimately, student satisfaction depends on the convergence of the student's expectations regarding these dimensions with the student's overarching educational and life goals for taking the course.